Кинетические закономерности протекания гетерогенно-каталитических процессов очистки газовых выбросов - Пономаренко, Анна Владимировна; Ведь, Валерий Евгеньевич; Варбанов, Петар; Сатаев, М. И. (НТУ "ХПИ", 2015)
Запропоновано залежність перебігу гетерогенно-каталітичного процесу окиснення газових викидів у кінетичній області на каталізаторі – Cо₃O₄, нанесеному на керамічний носій, з урахуванням впливу керуючих параметрів процесу: поверхневої концентрації каталізатору на носії, концентрації забруднюючих речовин у газовому потоці, швидкості газового потоку, зайнятої каталітичними сполуками площі носія.

A mathematical model of the heterogeneous catalytic process gas emissions oxidation course in the kinetic and external diffusion areas on the catalyst – Cо₃O₄ deposited on a ceramic carrier is suggested. The model contains parameters: surface catalyst concentration on the carrier, pollutants concentr ation in the gas flow, gas flow rate, the carrier area by catalytic compounds occupied.
Kinetic regularities of heterogeneous catalytic processes of gas emissions purification
Keywords: кинетическая область; газовый поток; химическая реакция; гетерогенно-каталитический нейтрализатор; температура